Dynamic temperature simulation of an accumulator in aircraft hydraulic systems - Jing Li; Xi Zhang; Yaobao Yin; Jianbo Zhang (2011 International Conference on Fluid Power and Mechatronics, 2011)
A mathematical model described the thermal characteristics of an accumulator is built up based on the first law of thermodynamics in this paper. The dynamic temperature calculation according to this model is finished in MATLAB and simulating the accumulator dynamic temperature under the system pressure pulsation and transient impact conditions respectively. The simulation analysis of an accumulator dynamic temperature in an aircraft hydraulic system show the oil temperature in the accumulator is related to the inlet oil temperature, the environment temperature and the inlet flow rate. This will provides theoretical fundament of quantitative thermal analysis for aircraft hydraulic systems.